PENETASAN TELUR DAN MORTALITAS PUPA NYAMUK Aedes aegypti PADA PERBEDAAN KONSENTRASI AIR REBUSAN SERAI (Andropogon nardus L) - Yusrina Ulfah; Abdul Gafur; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2009)
Aedes aegypti is the main vector of dengue (DBD) and Chikungunya disease. The mosquito eradication efforts with chemicals has negative impact, there for other alternative with optimal result and less negative effect are needed. One of the natural alternatives materials can be use is Andropogon nardus L. The conduct of this research is to know the effect of Andropogon nardus L on the hatch of egg and pupa mortality of Aedes aegypti. Research use completely randomized design with 5 treatments, which are control (concentration 0%), 5%, 10%, 15% and 20% concentration. The Anava result indicate that Andropogon nardus L with 0% concentration increase the time and level of egg hatch than the 20 % concentration. The Anava pupa mortality result indicate that young pupa have higher lethal amount than old pupa. The conclusion of the research are fragrant grass water can decrease the time and level of egg hatch and increase the mortality of Aedes aegypti pupa.